Avaliação do sinal eletromiográfico e da força de tronco e membros superiores em colaboradores da rede hoteleira: estudo observacional - Carvalho, Maryanne Martins Gomes de (2021)
Introduction: The rate of occupational diseases among workers of the hotel chain exceeds the average worker in the service sector, where the maids are in evidence as to the number of absenteeism. Muscle fatigue can trigger musculoskeletal disorders of occupational nature, away from the quality of life of millions of workers. Objectives: To evaluate the strength and electrical signals from the erector muscles of the spine very long, upper trapezius and middle deltoid chambermaid before and after the workday. Material and Methods: We evaluated 22 maids by recording the electrical signals from the erector muscles of the spine, upper trapezius and middle deltoid and the strength of the maids through a lumbar dynamometer. The volunteers made maximum force with lumbar transducer synchronized with electromyographic signals for 5 seconds. 3 questionnaires, one which analyzed personal data, pain intensity and predominant region were applied; another the Borg scale at the beginning and end of the activity, and finally, the questionnaire related to the activity day. Results: Only 7 collaborators (31.8%) reported no pain, all the remaining 15 (68.2%) reported collaborating. Of these, 5 (33.3%) have more than one location in pain: lower and upper back, knee and ankle. Borg scale indicated moderate exertion at the end of the workday. The force and angle of trunk flexion showed no statistically significant differences at p <0.05. Surface electromyography of the right middle deltoid before and after the work day showed statistically significant differences normalized by the peak in the collection, with RMS values of 74.80 (43.11 -87.33) and after the workday 52.55 (28.24 to 78.52), with P value = 0.009. The same occurred for the left middle deltoid muscle respectively with values before 62.32 (57.05 to 79.20) and after 48.55 (39.41 to 68.35), p = 0.001. The right trapezius muscle showed differences with 110.91 (52.84 to 150.85) and after 44.21 (23.24 to 89.61) with p = 0.020. Conclusion: Surface electromyography and dynamometry shown to be a reliable and effective tool in recognition of muscle work may be recommended to evaluate maids function after training.